Recent Progress in Artificial Muscles for Interactive Soft Robotics. Issue 19 (27th October 2020) - Wang, Jiangxin; Gao, Dace; Lee, Pooi See
Abstract: Artificial muscles are the core components of the smart and interactive soft robotic systems, providing the capabilities in shape morphing, manipulation, and mobility. Intense research efforts in the development of artificial muscles are based on the dielectric elastomer actuators, pneumatic actuators, electrochemical actuators, soft magnetic actuators, and stimulus responsive polymers. Recent progress has presented artificial muscles with impressive specific power output exceeding that of the natural muscles, dexterous shape morphing behavior that can be programmed and reconfigured, and exceptional high maneuverability to traverse surfaces with obstacles and different textures. Here, a succinct and critical summary is provided on the materials and strategies that have contributed to the important advancement of the artificial muscles in recent research. On that basis, the exciting opportunities are discussed in the integration of soft electronic devices with artificial muscles to enable smart and interactive soft robotic systems. Abstract : Artificial muscles are the core components of smart and interactive soft robotic systems. The recent new materials and strategies discovered to enable impressive development of the artificial muscles are highlighted. On that basis, discussion of the exciting opportunities in the integration of soft electronic devices with artificial muscles to enable interactive soft robotic systems is provided.